Multiplicity of perceptions on the sequelae of childhood sexual abuse : development of an empirical framework : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Pechtel, Pia (Massey University, 2008)
After over 30 years of research, our knowledge of the consequences of childhood sexual abuse (CSA) is still marked by considerable disarray. A research programme of three studies was designed to improve our understanding of functioning in adulthood after CSA by considering perceptions of sexual abuse from three different viewpoints: Clients with a history of CSA, lay, non-abused adults, and sexual abuse practitioners. In the first study, Multidimensional scaling was employed to develop a reporting device summarising the wide range effects and coping efforts likely to following sexual abuse (RESA – Reporting Effects of Sexual Abuse). A two-fold mapping and profiling approach was then used to highlight consistency and specificity of sexual abuse sequelae by comparing effect-coping patterns of 113 adults with a history of CSA to profiles describing the functioning of nontraumatised adults. The second study then enquired about the stability of perceptions of CSA consequences carried by 149 lay, non-abused adults. An analogue priming study explored how the impact of emotional arousal and cognitive re-structuring intervention adjust participants’ understanding of CSA outcomes. As lay, non-abused adults were found to carry an oversimplified perception of CSA sequelae, Study Three therefore investigated if practitioners were exempt from such underlying biases. Signal detection analysis was used in the final third study to independently assess 85 practitioners’ judgment accuracy and bias when asked to identify sexual abuse effects among a set of supposedly unrelated behaviour, and to discriminate direct effects from secondary ways of coping with CSA. While practitioners were successful in detecting relevant CSA sequelae, they nonetheless demonstrated a highly overinclusive perception compared to the empirical reports by sexually abused clients and societal perceptions. Findings of the three studies were integrated to build an empirical framework on the multiplicity of perceptions on the sequelae of CSA. Overall, this research showed that all individuals, regardless of their association with CSA, carry perceptions about the consequences of CSA. These perceptions appeared to be universal, independent of emotional arousal or attempted cognitive restructuring. While CSA clients reported an array of effects and coping efforts, society only seemed to reflect basic elements of these as related to CSA. Professionals, on the other hand, indicated overinclusive perceptions in which most characteristics were identified as CSA sequelae, in particular as a mean of coping. Finally, no specific pathway was found to follow CSA. While there appeared to be an increased intensity of effects and a greater need for coping among adults with a history of CSA, the general pattern or type of sequelae was also reported by non-traumatised adults. Understanding the functional processes underlying these patterns of common sequelae can help to tailor treatment to the individual needs of clients who experienced CSA. Further implications of this empirical model for practice and research in the area of sexual abuse in Aotearoa/New Zealand are discussed.
Keywords: Child sexual abuse; Adult child sexual abuse victims; Sexual abuse; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology